The Relationship Between Knowledge, Attitude, and Behavior Factors With the Implementation of Smoke-Free Areas in the Campus Environment: Literature Review - Putri, Hanan Aliya; Umaroh, Ayu Khoirotul (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: The prevalence of smoking among Indonesians aged >/ 15 years was 36.3% in 2013 and decreased to 33.8% in 2018 (Riskesdas). The Smoke-Free Area (SFA) policy aims to minimize the adverse health impacts of smoking. Compliance in campus settings requires the academic community to follow regulations, such as refraining from smoking in designated SFA zones. Objective: To identify significant factors knowledge, attitudes, and behaviors associated with compliance to the SFA policy in the campus environment. Methods: A literature review was conducted following the PRISMA approach, using databases including Google Scholar, PubMed, and ScienceDirect. Inclusion criteria were full-text articles, quantitative cross-sectional studies with bivariate analysis, published in Indonesian or English between 2013–2023. Results: Four eligible articles were reviewed. Two focused on knowledge as a factor, two on attitudes, and one on behaviors influencing compliance. Findings indicate that higher knowledge levels, positive attitudes, and supportive behaviors contribute to improved adherence to SFA implementation in campuses. Conclusion: Knowledge, attitudes, and behaviors are significant factors in enhancing compliance with SFA policies. Promoting awareness and cultivating positive behavioral changes among the academic community can strengthen the success of smoke-free campus initiatives